The Australian Taxation Office's collection and management of activity statement information : Australian Taxation Office - Australian National Audit Office; Hansen, Jon. (Canberra : Australian National Audit Office, 2004)
Activity statements comprise the Business Activity Statement (BAS) and Instalment Activity Statement (IAS) which are used to report and/or remit multiple Commonwealth taxes. The management of activity statements is important as approximately 65% of revenue collected by the ATO was received through activity statements in 2002-03.
"Audit team: Jon Hansen, Katherine Buchanan, Kieth Allen, Peter White"--P. 4.
Includes index.
Includes bibliographical references.
Also available in an electronic version via the Internet. Address as at 19/4/04: http://www.anao.gov.au/WebSite.nsf/Publications/68A6DF0DD80C30F6CA256E4B006FCF6B
System requirements: Adobe Acrobat Reader required to view/print PDF files.
Keywords: Australian Taxation Office -- Auditing; Tax administration and procedure -- Australia -- Auditing; Value-added tax -- Australia